Immunologists' Perspectives on Monogenic Inflammatory Bowel Diseases - Maryiam Jama Ali Osman; Emine Selva Aydoğdu; Rafah Mackeh; Ahmet Özen; Bernice Lo (Turkish Journal of Immunology)
Inflammatory bowel diseases (IBD) encompass a group of chronic inflammatory disorders primarily impacting the gastrointestinal system, and they may also affect other organ systems. While common forms of IBD typically arise from multifactorial causes, there exists a subset of patients with single gene defects known as monogenic IBD (mIBD). Over 100 genes have been associated with mIBD, spanning various biological pathways which affect various tissues; the immune system is the most commonly involved, but more rarely, the intestinal epithelium is the primarily affected compartment. Timely diagnosis hinges on awareness and the application of contemporary molecular techniques. Due to the diverse range of causes, managing mIBD requires a multidisciplinary approach. Conventional treatments often fall short, necessitating a personalized strategy that considers the multifaceted nature of mIBD presentations and the diverse etiologic factors. In recent times, novel therapies have emerged, targeting specific causative genes or affected pathways. This discussion delves into the fundamental aspects of mIBD, with particular emphasis on recent breakthroughs in the field, encompassing newly identified gene defects and innovative management strategies.